2008
DOI: 10.1007/s00192-008-0734-4
|View full text |Cite
|
Sign up to set email alerts
|

Is there any evidence to advocate SUI prevention in continent women undergoing prolapse repair? An overview

Abstract: Postoperative SUI prevention at the time of prolapse surgery is still a challenging issue. Recent findings suggested that a systematic prophylactic Burch colposuspension could be performed in continent women undergoing a sacral colpopexy. The aim of this paper is to collect relevant literature in order to suggest a management strategy. A thorough PubMed research of all papers in the English language was conducted. Evidence-based medicine was analyzed and current unanswered questions were discussed. Despite evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 55 publications
0
26
0
4
Order By: Relevance
“…Earlier reviews and studies suggested the same, but evidence for this is still limited. 2,[46][47][48] It remains a problem that there is no consensus in diagnosing occult SUI, and different methods to detect occult SUI were used in the studies included in our review.…”
Section: Interpretation In the Light Of Other Evidencementioning
confidence: 99%
“…Earlier reviews and studies suggested the same, but evidence for this is still limited. 2,[46][47][48] It remains a problem that there is no consensus in diagnosing occult SUI, and different methods to detect occult SUI were used in the studies included in our review.…”
Section: Interpretation In the Light Of Other Evidencementioning
confidence: 99%
“…Their study utilized the transvaginal mesh in contrast to transobturator mesh which has a higher bladder perforation rate as reported by other authors. [13][14][15][16] Our study did not report any significant difference between the two groups for incidence of urinary tract infection (p=0.672). This was in contrast to the findings of the OPUS trial 18 where the difference was significant (p=0.008).…”
Section: Proceedings In Obstetrics and Gynecology 2017;7(1):6mentioning
confidence: 81%
“…However, some authors advocate placement of a suburethral sling by systematic approach, taking into account the patients' variables and their own goals of therapy. [13][14][15][16] Several studies have been conducted to assess the benefits and effects of a prophylactic sling surgery. Various studies have evaluated this in the context of abdominal surgery, for example, Burch colposuspension 7,8 and vaginal procedures, such as, transvaginal tape [18][19][20][21] and transobturator tape 22 approach.…”
Section: Prophylactic Midurethral Slingmentioning
confidence: 99%
“…The anterior repair with mesh raises the risk for postoperative SUI from 10% to 23% compared to traditional colporraphy [14]. Antiincontinence operations in association with vaginal surgery are reportedly an efficient treatment of occult SUI [19], but the risk for urinary retention must be taken into consideration [20,21]. Therefore, although routine preoperative stress test might be positive, one must consider carefully whether concomitant SUI surgery is essential.…”
Section: Discussionmentioning
confidence: 99%